The Influence of Organizational Communication Climate and Leaderships Comunication on Employee’s Work Motivation on Faculty of Farm Science, Jenderal Soedirman University Purwokerto - Budi Wirawan, Kukuh; Suprihartini, M.Si, Dra. Taufik (Interaksi Online, 2016)
This Research was based by Indonesia’s government policy to given theperformance compensation to all employee that works on Civil University acrossIndonesia. The policy to given the performance compensation itself was arranged onPerpres No. 88 Tahun 2013 and Peraturan Menteri Pendidikan dan Kebudayaan no.107 Tahun 2013. This policy is aim to motivate all employee that works on CivilUniversity in Indonesia to increased or keep their work motivation in a good condition.However, this policy wasn’t given any effects on employee’s work motivation inFaculty of Farm Science, Jenderal Soedirman University. The employee’s workmotivation in Faculty of Farm Science, Jenderal Soedirman University is still not in agood condition, indicated by the high number of indiciplinary action done by theemployee, and the low number of participants in the job promotion test. After doing pre- research survey, the researcher finds out that there is an issue about lack of trustbetween the employee and their leaders, lack of coordination between staff and theirleaders, and the leaders that not listened to complain, idea, and opinion shared by theirstaff. This issue indicating there is a problem in Organizational CommunicationClimate and Leaderships Communications between the Employee and their leaders inFaculty of Farm Science, Jenderal Soedirman University.This research is aim to find out the influence of Organizational CommunicationClimate and Leaderships Communications on Employee’s Work Motivations. TheConcept that used in this research is Organizational Communication Climate conceptby Wayne Pace and Don F. Faules (Pace and Faules, 2010 :156) and LeadershipsCommunication Concept by Abdullah Masmuh (2008:280). The population on thisresearch is 68 civil servant that works in Faculty of Farm Science, Jenderal SoedirmanUniversity. The Sampling method used in this research is total sampling method, andthe data will be analyzed using simple linear regression analysis with the help of SPSSVersion 20 Software.The result from the research conclude that Organizational CommunicationClimate affected Employee’s work motivation in positive way. That means if thecondition of Organizational Communication Climate gets better, the employee workmotivation will be increased. The results showed the value of F Significance is 0,001which means there is significance influence between Organizational CommunicationClimate and Employee Work Motivations (0,001<0,05), And the value of regressioncoefficient is 0,275, indicating that the influence given by OrganizationalCommunication Climate to Employee Work Motivation is in positive way. The resultalso conclude that Leaderships Communication also has affected Employee’s WorkMotivation in positive way. That means when condition of Leadership Communicationbetter, the employee work motivation will be increased. The results ashowed the valueof F significance is 0,014. Which means there is significance influence betweenLeaderships Communications and Employee Work Motivations (0,014<0,05), and thevalue of regression coefficient is 0,330, indicating that influenced given by LeadershipsCommunications to Employee Work Motivations is in Positive Way.